How to Envision Critical Ethnography within Qualitative Research? - Vargas-Jiménez, Ileana (2015)
In the first place, the article intends to get closer to what qualitative research is. Subsequently, throughout reflection, ethnography is considered in more detail, and, for this, its origin and foundations are mentioned. Then, the results of several investigations are disclosed as well as some trends of research in critical ethnography are indicated. The author wants to rescue the fact that from the bibliographical search carried out there was a case illustrating what critical ethnography is and how it is linked to research. The main conclusions highlighted that critical ethnography works not only to listen to complaints in a critical and reflective way, but to vigorously denounce, respecting the voices and approaches: this is what critical ethnography tries to rescue from its participants through their stories and experiences.